GLOBALIZATION'S IMPACT ON INTERNATIONAL TRADE: OPPORTUNITIES AND CHALLENGES - Misbah Mehraj (RADJA PUBLIKA, 2023)
Globalization has profoundly reshaped international trade dynamics over the past few decades, presenting both unprecedented opportunities and daunting challenges for economies worldwide. This paper examines the multifaceted impacts of globalization on international trade, focusing on how it has transformed the global economic landscape. Through a comprehensive review of existing literature and empirical evidence, the paper explores the opportunities arising from increased market access and integration, technological advancements, and enhanced specialization. Concurrently, it addresses the challenges posed by heightened competition, income inequality, and environmental sustainability concerns. By analyzing these factors, the paper aims to provide a balanced perspective on globalization's influence on international trade and offers insights into strategic approaches for policymakers and businesses to navigate this complex terrain effectively.